SMARTBELL SEBAGAI APLIKASI IoT PADA SISTEM KEAMANAN RUMAH - Dale Watson; Hendra Tjahyadi (Journal Information System Development (ISD), 2022)
In this paper, a smart bell system is designed and realized. The system uses a passive-infrared sensor to detect motion and activate the system to logged detection time to database, sent notification, and command a webcam to take pictures and record video. An Arduino microcontroller is used to process data that will be presented on web pages which are then converted into Progressive Web Applications. Node.js is used as the platform to creare a server, and MongoDB is employed as database for time detection. For communication system protocol between the database and web application pages the REST-API method is used. During the detection process, the system will send a notification using webpush with the Firebase Cloud Messanging framework. The system was tested to detect, record videos, create GIFs, write to databases, and send notifications into web applications. The experiments shows a success of 81.25% for displaying videos and of 93.75% for displaying GIFs.